2020
DOI: 10.1136/oemed-2020-107005
|View full text |Cite
|
Sign up to set email alerts
|

Update on the epidemiology of work-related traumatic brain injury: a systematic review and meta-analysis

Abstract: BackgroundTraumatic brain injury (TBI) is a public health concern that can occur in a range of contexts. Work-related TBI (wrTBI) is particularly concerning. Despite overall work-related injury claims decreasing, the proportion of claims that are wrTBI have increased, suggesting prevention and support of wrTBI requires ongoing attention.ObjectivesThis review aimed to provide updated information on the burden and risk factors of wrTBI among the working adult population.MethodsMedline, Embase, PsycINFO, and Cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Work-related traumatic brain injury (TBI) accounts for 18% of the estimated 1.7 million TBIs that occur in the Unites States annually. [1,2] It is among the most serious and disruptive occupational injuries, as those surviving TBI can face long-term cognitive, psychological and emotional impairments. [3,4] The economic burden of treatment for severe TBI ranges from $600,000 to $1,8 million per case, not including the value of lost productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work-related traumatic brain injury (TBI) accounts for 18% of the estimated 1.7 million TBIs that occur in the Unites States annually. [1,2] It is among the most serious and disruptive occupational injuries, as those surviving TBI can face long-term cognitive, psychological and emotional impairments. [3,4] The economic burden of treatment for severe TBI ranges from $600,000 to $1,8 million per case, not including the value of lost productivity.…”
Section: Introductionmentioning
confidence: 99%
“…[8] A 2021 systematic review found that despite a decrease in overall work-related injury claims, the proportion of claims from work-related TBIs have increased. [2] This suggests that advancing preventative safety technology remains an urgent matter to address the costly and debilitating TBI epidemic among the work force.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, CBI is one of the leading causes of death in addition to cardiovascular disease and cancer (3). A histogram of age-related CBI shows a bimodal distribution with the first and second maximums for subjects aged 15 and >75 years old, respectively (4). CBI is more common amongst men than among women, showing a ratio between 1.9:1-2.8:1 (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…TBI includes noncongenital tissue damage rendered by a sudden impact manifested by endocrine dysfunction, electrolyte imbalance, respiratory manifestations, and neurological, neuropsychological, and psychiatric dysfunction [ 2 ]. TBI occurs most frequently in two age groups: between 15 and 24 and older than 75 years of age [ 3 ]. Although TBI is prevalent internationally at 1.3 and 2 per 100,000 in North America and Europe, respectively, in Poland, its frequency oscillates around 0.07 per 100,000.…”
Section: Introductionmentioning
confidence: 99%